Radiographic and Postoperative Outcomes of Plate Versus Screw Constructs in Open Reduction and Internal Fixation of Calcaneus Fractures via the Sinus Tarsi. (August 2019) - Pitts, Charles C.; Almaguer, Adam; Wilson, John T.; Quade, Jonathan H.; Johnson, Michael D.
Background: Intra-articular fractures of the calcaneus are a common injury to the hindfoot following high-energy trauma to the lower extremity. Treatment of these fractures has evolved. Due to the concern of wound complications associated with extensile open treatment, smaller incision techniques, such as the sinus tarsi approach, are increasing in popularity. A number of fixation strategies are utilized with this approach, and it is unknown which most accurately restores radiographic alignment. The purpose of this study was to compare the postoperative radiographic outcomes of a plate and screw construct versus a cannulated screw construct when using the sinus tarsi approach for open reduction and internal fixation (ORIF) of calcaneus fractures. Methods: After institutional review board approval, records for all patients treated surgically at our institution for calcaneus fractures from 2012 to 2017 were reviewed. Inclusion criteria were intra-articular calcaneus fractures, patients aged 18 years or older, and use of the sinus tarsi approach. Exclusion criteria were open fractures and fractures with less than 6 weeks of postoperative weightbearing, which were excluded for radiographic outcomes. A total of 51 fractures underwent ORIF using cannulated screws alone (group 1), and 23 fractures underwent ORIF using a sinus tarsi plate (group 2). Sixty-one fractures (41 vs 20, respectively) met criteria for radiographic comparison. The primary outcomes of interest included pre- and postoperative Bohler and Gissane angles, wound complications, unplanned return to the operating room (OR), and cost comparison. Results: There was no statistically significant difference between preoperative Bohler angles for group 1 (14.4 degrees) versus group 2 (12.2 degrees) ( P = .44), nor was there a significant difference between postoperative Bohler angles for group 1 (30.1 degrees) versus group 2 (27.1 degrees) ( P = .14). Similarly, preoperative Gissane angles for group 1 (130.5 degrees) and group 2 (133.4 degrees) ( P = .54) and postoperative Gissane angles for group 1 (118.2 degrees) and group 2 (119.8 degrees) ( P = .44) showed no statistically significant difference. There were a total of 3 wound complications in group 1 versus 2 wound complications in group 2 ( P = .66). There was no statistically significant difference in operative duration ( P = .97) or the number of unplanned returns to the OR between the 2 groups ( P = .68). Based on the implants used at this institution, and depending on the number of screws used, the estimated cost range of a plate construct was $1070 to $1235, while the estimated cost range of a cannulated screw construct was $717 to $1264. Conclusion: When comparing the cannulated screw and plate and screw fixation techniques, there was no difference in restoration of the Bohler and Gissane angles. Furthermore, the amount of angular correction achieved by initial reduction showed no statistically significant difference between groups, and the amount of reduction lost between initial and final postoperative radiographs showed no statistically significant difference between groups. With regard to the 2 techniques, there was no statistically significant difference in rates of postoperative complications and return to the OR. Our data suggest that fixation using cannulated screws alone versus sinus tarsi plate provides similar radiographic outcomes and risk of complications. The 2 techniques were also similar in terms of implant costs. Our results indicate that either technique effectively improved radiographic parameters. Level of Evidence: Level III, retrospective comparative study.